2023
DOI: 10.1097/ms9.0000000000000401
|View full text |Cite
|
Sign up to set email alerts
|

Management of appendicitis: appendicectomy, antibiotic therapy, or both?

Abstract: Introduction: Appendicitis is a global disease with an incidence of 7–12% in the population of the USA and Europe but is low and rising in the developing world. It is the most common acute general surgical emergency, but as no investigation is accurate, the diagnosis has to rely on clinical symptoms and signs and, thus, frequently misdiagnosed. The aim of the study was to debate the arguments for managing appendicitis (operative, nonoperative, or both). Patients and methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…However, there is no evidence to indicate the proportion of patients likely to develop diffuse sepsis because the antibiotic treatment alters the pattern of disease by replacing the risks of perforation with the lesser risk associated with surgery. 2 Several older studies, including two meta-analyses of complicated appendicitis, have shown that immediate operative management is associated with higher rates of complications. On the other hand, a small randomized trial in adults with an abscess demonstrated that immediate laparoscopic surgery was associated with fewer readmissions and CT scans, as well as fewer complications and re-interventions.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no evidence to indicate the proportion of patients likely to develop diffuse sepsis because the antibiotic treatment alters the pattern of disease by replacing the risks of perforation with the lesser risk associated with surgery. 2 Several older studies, including two meta-analyses of complicated appendicitis, have shown that immediate operative management is associated with higher rates of complications. On the other hand, a small randomized trial in adults with an abscess demonstrated that immediate laparoscopic surgery was associated with fewer readmissions and CT scans, as well as fewer complications and re-interventions.…”
Section: Introductionmentioning
confidence: 99%